2015
DOI: 10.1128/iai.02633-14
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Encoded MCP Is Involved in Virulence, Motility, and Biofilm Formation of Cronobacter sakazakii ATCC 29544

Abstract: bThe aim of this study was to elucidate the function of the plasmid-borne mcp (methyl-accepting chemotaxis protein) gene, which plays pleiotropic roles in Cronobacter sakazakii ATCC 29544. By searching for virulence factors using a random transposon insertion mutant library, we identified and sequenced a new plasmid, pCSA2, in C. sakazakii ATCC 29544. An in silico analysis of pCSA2 revealed that it included six putative open reading frames, and one of them was mcp. The mcp mutant was defective for invasion int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 67 publications
(65 reference statements)
1
23
1
Order By: Relevance
“…96 It was also observed that this sequence was not found in any other lineages, implying that the MCP association with virulence is probably specific to the ST8 lineage.…”
Section: Biofilm Formationmentioning
confidence: 82%
“…96 It was also observed that this sequence was not found in any other lineages, implying that the MCP association with virulence is probably specific to the ST8 lineage.…”
Section: Biofilm Formationmentioning
confidence: 82%
“…One possibility is that adhesins, which are present in the polar region of the cells or secreted at this location, stabilize the cell-cell contacts in clumps, akin to a similar adhesion described in closely related alphaproteobacteria (59)(60)(61). Flocculation is widespread in many motile bacteria capable of chemotaxis, and chemotaxis defects have been linked to increased cell aggregation in many bacterial species (62)(63)(64). It is thus likely that chemotaxis-dependent clumping occurs in other bacterial species.…”
Section: Chemotaxis Control Of Flagellar Motility and Clumping In Azomentioning
confidence: 99%
“…A notable finding was the presence of a gene with homology to methyl-accepting chemotaxis protein (MCP) on the 4,938 bp-ColRNA1 plasmid. The same gene present on plasmid pCSA2 of Cronobacter sakazakii ATCC29544 was previously shown to be involved in adhesion, invasion, and the regulation of mobility and biofilm formation in that isolate (11). …”
Section: Genome Announcementmentioning
confidence: 93%